Badania marketingowe w przedsiębiorstwach działających na rynkach międzynarodowych - Jaciow, Magdalena (Marketing Research in Enterprises on International Markets, 2006)
The article presents research results which aim is to find out the opinion about marketing research among managers working in international enterprises. The article gives also the answer about the level of information usage during decision process and the efficiency of marketing research done in those companies.The research results show very big importance of doing marketing research in international enterprises. There is a significant level of usage of information gathered during the research in decisions taking. The marketing research is also recognized as effective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 98-105